A method for preparing a low-salt permeable bipolar membrane
The low-salt permeable bipolar membrane is prepared through a multi-step process, including the preparation of the male film layer, the catalytic layer, the first female film layer and the second female film layer, and the film layers are fixed together through the hot melt process, solving the problem of high salt permeability in the prior art, and achieving a bipolar membrane with low salt permeability and low hydrolysis voltage.
Patent Information
- Application Number
- CN202411804581.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing bipolar membrane preparation process is difficult to form a crosslinked structure, resulting in high salt permeability effect and salt contamination in acids and alkalis, reducing the current efficiency of the hydrolysis process.
A low-salt permeable bipolar film is prepared by a multi-step process, including the preparation of a male film layer, a catalytic layer, a first female film layer and a second female film layer. Each film layer is fixed together through a hot melt process to form an integral bipolar film. The first vaginal film layer is designed to be thin and does not contain crosslinking agents, and the second vaginal film layer is a highly selective membrane layer to ensure low salt permeability of the bipolar film.
The low salt permeability and low hydrolysis voltage of the bipolar membrane are achieved, which reduces salt pollution in acids and alkalis and improves the current efficiency of the hydrolysis process.
Smart Images

Figure CN119258795B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of bipolar membrane preparation, and in particular, relates to a method for preparing a low-salt permeable bipolar membrane. Background Art
[0002] The bipolar membrane is a composite membrane composed of a cation exchange membrane layer (referred to as the cation membrane layer), an intermediate catalytic layer (referred to as the intermediate layer or catalytic layer) and an anion exchange membrane layer (referred to as the anion membrane layer); under the action of an external electric field, the water molecules in the bipolar membrane will quickly dissociate into hydrogen ions and hydroxides, that is, water dissociation occurs, and the hydrogen ions and hydroxides migrate through the cation membrane layer and the anion membrane layer respectively under the action of the electric field to form acid and alkali solutions on both sides of the bipolar membrane; based on the water dissociation characteristics of the bipolar membrane, the bipolar membrane is matched with a cation exchange membrane (referred to as the cation membrane) and an anion exchange membrane (referred to as the anion membrane) to form a bipolar membrane electrodialysis device, which can convert salt into corresponding acids and bases under the action of an electric field, such as converting sodium chloride into hydrochloric acid and sodium hydroxide, or converting sodium sulfate into sulfuric acid and sodium hydroxide.
[0003] The selectivity of ion exchange membrane, that is, its ability to block the permeation of common ions, is close to and less than 100%, and continues to decrease with the increase of external solution concentration; since the selectivity of the cation layer and anion layer of the bipolar membrane cannot reach 100%, when water is dissociated, hydrogen ions and hydroxides enter the acid chamber and alkaline chamber from the middle layer through the cation layer and anion layer respectively. At the same time, a certain amount of chloride ions (or sulfate ions) enter the middle layer from the acid chamber through the cation layer and further migrate to the alkaline chamber, and a certain amount of sodium ions enter the middle layer from the alkaline chamber through the anion layer and further migrate to the acid chamber, so that both the acid and the base contain a certain amount of salt (sodium chloride or sodium sulfate), which is called salt contamination; the migration of salt ions accompanied by the water dissociation process of the bipolar membrane, that is, salt penetration, will reduce the purity of the acid and the base, and also reduce the current efficiency of the water dissociation process. Bipolar membranes with low salt penetration can solve the above problems.
[0004] In the prior art, the bipolar membrane is prepared by bonding the cation layer and the anion layer together (i.e. bonding process, such as German patent DE3508206A) or hot pressing them together (i.e. hot pressing process, such as U.S. patent US5401408A) to obtain the bipolar membrane. The bonding force between the two membrane layers is often insufficient, which may lead to the separation of the two membrane layers in the application of the bipolar membrane. The polymer solutions of the cation layer and the anion layer are co-extruded at an elevated temperature (i.e. co-extrusion process, such as Bipolar Membrane Technology Handbook (ISBN 9787502555733), Chapter 4, pages 85-89), the resins of the two membrane layers diffuse into each other, resulting in too high resistance of the middle layer and too high water dissociation voltage of the bipolar membrane; the monolithic bipolar membrane is formed by chemical reaction on both sides of the same substrate (such as US Pat. No. 5,840,192A), and it is difficult to control the interface structure of the middle layer and optimize the electrochemical properties of the two membrane layers. The water dissociation voltage and salt permeability of the bipolar membrane are both high; the most typical bipolar membrane preparation process is casting, that is, first preparing the cation membrane, and then coating the surface of the cation membrane with The catalyst is decomposed into water and then coated with a polymer solution of the anion membrane to obtain the anion membrane layer of the bipolar membrane, such as U.S. Patent US4851100A and German Patent DE4026154A. This process can optimize the electrochemical performance of the cation membrane layer and the interface structure and catalyst dosage of the intermediate layer. However, the anion membrane layer cannot form a cross-linked structure (cross-linked polymers are usually unable to dissolve to form a coating solution), resulting in insufficient selectivity of the membrane layer and higher salt penetration, or a subsequent chemical reaction must be used to introduce a cross-linked structure into the anion membrane layer, but this will affect the performance of the cation membrane layer and the structure and catalytic properties of the intermediate layer. Summary of the invention
[0005] The purpose of the present application is to provide a method for preparing a low-salt permeable bipolar membrane to solve the technical problems that the bipolar membrane prepared by the prior art is difficult to form a cross-linked structure, has a high salt permeability effect, and produces obvious acid and alkali salt pollution.
[0006] To achieve the above object, the technical solution adopted in the present application is: to provide a method for preparing a low-salt permeable bipolar membrane, which specifically comprises the following steps:
[0007] (i) preparing a cationic membrane layer: preparing a cationic membrane monomer solution, wherein the cationic membrane monomer solution includes a cationic membrane functional monomer, a cross-linking agent, an organic solvent and an initiator; soaking a substrate in the cationic membrane monomer solution and then placing the substrate between two inert sheets, removing bubbles to obtain a cationic membrane complex, and heating the cationic membrane complex to perform a polymerization reaction; and peeling off the inert sheets to obtain a cationic membrane layer;
[0008] (ii) preparing the catalytic layer: coating a catalyst dispersion on one side of the cation film layer to form a catalytic layer on the surface of the cation film layer;
[0009] (iii) preparing the first anion membrane layer: coating the coating liquid prepared by solution polymerization of anion membrane functional monomers and anion membrane comonomers on the catalyst layer, and drying to form the first anion membrane layer on the surface of the catalyst layer to obtain a composite membrane;
[0010] (IV) preparing the second anion membrane layer: preparing anion membrane monomer solution, the anion membrane monomer solution comprising anion membrane functional monomer, a cross-linking agent, an organic solvent and an initiator; soaking the microporous membrane in the anion membrane monomer solution and then placing it between two inert sheets, removing bubbles to obtain an anion membrane complex, heating the anion membrane complex to perform a polymerization reaction; peeling off the inert sheets to obtain the second anion membrane layer;
[0011] (V) Preparation of bipolar membrane: The second anion membrane layer is tightly attached to the first anion membrane layer of the composite membrane; through a hot melt process, a hot melting point is formed between the second anion membrane layer and the composite membrane to obtain a low-salt permeability bipolar membrane.
[0012] In one embodiment,
[0013] Step (i) the cationic functional monomer is an organic ammonium salt of styrene sulfonate, and the organic ammonium salt of styrene sulfonate is one of trimethylamine styrene sulfonate, triethylamine styrene sulfonate, pyridinium styrene sulfonate or N-methylimidazole styrene sulfonate; the crosslinking agent is p-divinylbenzene; the organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide; the initiator is one of azobisisobutyronitrile, azobisisoheptylnitrile or dibenzoyl peroxide; preferably, the cationic functional monomer is trimethylamine styrene sulfonate, the organic solvent is N-methylpyrrolidone, and the initiator is azobisisobutyronitrile;
[0014] In step (i), the molar ratio of the cross-linking agent to the cationic functional monomer is 2-4:8-6, preferably, the molar ratio of the cross-linking agent to the cationic functional monomer is 4:8;
[0015] Furthermore, a cationic comonomer is added to the cationic monomer solution, the cationic comonomer is acrylic acid or methacrylic acid, the molar ratio of the cationic comonomer to the cationic functional monomer is 0-4:10-6, preferably, the molar ratio of the cationic comonomer to the cationic functional monomer is 4:8; the cationic functional monomer, the cationic comonomer and the crosslinking agent constitute a polymerizable component;
[0016] In this embodiment, organic ammonium styrene sulfonate is used to replace the more common sodium styrene sulfonate or styrene sulfonic acid, so that the organic ammonium styrene sulfonate can be more easily polymerized to form a high molecular weight polymer. For this purpose, sodium styrene sulfonate or styrene sulfonic acid needs to be converted into organic ammonium styrene sulfonate by a chemical reaction (for example, sodium styrene sulfonate is reacted with trimethylamine hydrochloride to obtain trimethylamine styrene sulfonate and precipitate sodium chloride); too high a cross-linking agent content will lead to high resistance of the cation membrane, and ultimately the water dissociation voltage of the bipolar membrane will be higher. Too low a cross-linking agent content will lead to high swelling rate and low selectivity of the cation membrane, and ultimately the bipolar membrane will have high salt leakage; adding a cation membrane comonomer, the cation membrane functional monomer and the cation membrane comonomer and the cross-linking agent undergo a copolymerization reaction, which helps to polymerize to form a high molecular weight polymer, so that the cation membrane layer has lower swelling and higher selectivity.
[0017] In one embodiment,
[0018] Step (i) The substrate is prepared by bonding non-woven fabric layers on both sides of the microporous membrane, the material of the microporous membrane is polyethylene, polypropylene or one of ethylene and propylene copolymers, the material of the non-woven fabric layer is polyethylene, polypropylene or one of ethylene and propylene copolymers, and the porosity of the microporous membrane is 40-70%;
[0019] In this embodiment, the microporous membrane and the non-woven fabric layer do not need to be made of the same material. For example, a polyethylene microporous membrane and a polypropylene non-woven fabric layer can be selected to form the substrate; the use of polyolefins with a lower melting point helps to better thermally fuse the two membrane layers in the subsequent steps; the porosity of the microporous membrane is related to the amount of polymer filled in the microporous membrane. The less the amount of polymer filled, the higher the membrane resistance, and the more the amount of polymer filled, the higher the membrane swelling and the lower the selectivity; the non-woven fabric layer is formed on the surface of the microporous membrane, making the membrane surface rougher or easily roughened by mechanical grinding, which can make the positive membrane layer and the catalytic layer have a stronger bonding force; the second negative membrane layer uses a microporous membrane as a supporting cloth, and there is no need to form a non-woven fabric layer on the surface of the microporous membrane, because other membrane layers are subsequently composited through a thermal fusion process.
[0020] In one embodiment,
[0021] The heating temperature in step (i) is 60-100°C for 8-24 h, preferably 80°C for 16 h; the inert sheet is made of plastic, glass or metal, preferably polyethylene terephthalate film;
[0022] In this embodiment, if the polymerization temperature is too low, a longer polymerization time is required, and if the polymerization temperature is too high, the structure of the microporous membrane of the polyolefin material will be destroyed. After comparing multiple embodiments, the optimal temperature is selected to be 80°C.
[0023] In one embodiment,
[0024] Step (ii) The catalyst dispersion is prepared by dispersing one of chloride, sulfate or nitrate of trivalent chromium or trivalent iron in an alkaline solution, or dispersing one of titanium dioxide, tin dioxide or ruthenium dioxide in pure water; the concentration of the catalyst dispersion is 0.5-5%, preferably, the concentration of the catalyst dispersion is 3%;
[0025] In this embodiment, the catalyst dispersion can be dispersed onto the surface of the cation membrane layer by rotary spraying or ultrasonic spraying, or the catalyst dispersion can be directly scraped onto the surface of the cation membrane layer; if the catalyst loading on the membrane surface is too little, the water dissociation voltage of the bipolar membrane will be high, and if the loading is too much, it will affect the bonding force between the subsequent first anion membrane layer and the cation membrane layer; when polishing the surface of the cation membrane layer, sandpaper or a hard brush can be used.
[0026] In one embodiment,
[0027] The anion membrane functional monomer is one of 1-methyl-4-vinylpyridinium iodide, 1-ethyl-4-vinylpyridinium iodide, 1-propyl-4-vinylpyridinium bromide, 1-vinyl-3-methylimidazolium iodide, 1-vinyl-3-ethylimidazolium iodide, and 1-vinyl-3-propylimidazolium bromide, and the anion membrane comonomer in step (iii) is styrene or p-methylstyrene; preferably, the anion membrane functional monomer is 1-vinyl-3-methylimidazolium iodide, and the anion membrane comonomer is p-methylstyrene;
[0028] In this embodiment, the anionic membrane comonomer does not contain a functional group. The addition of the anionic membrane comonomer makes the copolymerized polymer contain a hydrophobic structural unit, the polymer is insoluble in water, and both the polymer and the cationic membrane layer contain styrene structural units, which makes the polymer have a stronger bonding force with the cationic membrane layer; when preparing the coating liquid, an organic solvent and an initiator need to be added for solution polymerization.
[0029] In one embodiment,
[0030] In step (iii), the molar ratio of the anion membrane comonomer to the anion membrane functional monomer is 3-7:7-3. Preferably, the molar ratio of the anion membrane comonomer to the anion membrane functional monomer is 2:1.
[0031] In this embodiment, if the proportion of functional monomers is too high, the first cathodic membrane layer will swell, seriously affecting the bonding strength with the cation membrane. If the proportion of functional monomers is too low, the resistance of the first cathodic membrane layer will be high, resulting in a high water dissociation voltage of the bipolar membrane.
[0032] In one embodiment,
[0033] Step (iii) the drying temperature is 80-100°C for 0.5-2 h, preferably, the drying temperature is 80°C for 1 h; the thickness of the first cathode film layer is 10-40 μm, preferably, the thickness of the first cathode film layer is 20 μm;
[0034] In this embodiment, the thickness of the first cathodic membrane layer is set to be thinner, which can reduce the resistance of the membrane layer, thereby lowering the water dissociation voltage of the bipolar membrane.
[0035] In one embodiment,
[0036] Step (iv) the molar ratio of the crosslinking agent to the anionic membrane functional monomer is 2-5:8-5, preferably, the molar ratio of the crosslinking agent to the anionic membrane functional monomer is 1:2; the heating temperature is 60-100°C, the time is 4-24 h, preferably, the heating temperature is 80°C, and the time is 16 h;
[0037] In this embodiment, similar to the preparation of the cation membrane layer, too high a cross-linking agent content will lead to high resistance of the second anion membrane layer, and ultimately the bipolar membrane has a higher water dissociation voltage. Too low a cross-linking agent content will lead to a high swelling rate and low selectivity of the second anion membrane layer, and ultimately the bipolar membrane has a higher salt leakage. If the polymerization temperature is too low, a longer polymerization time is required. If the polymerization temperature is too high, the microporous membrane structure of the polyolefin material will be destroyed. After comparing multiple embodiments, the optimal temperature is selected to be 80°C.
[0038] In one embodiment,
[0039] The temperature of the heat fusion in step (V) should be higher than 100°C to ensure that the membrane layers can be fused together, but the temperature should not be too high. A temperature higher than 150°C may cause a melt-through defect at the heat melting point. Preferably, the heat fusion temperature is 110-130°C; the heat melting point diameter is 3-6 mm, and the heat melting point occupies an area of 2-20% of the low-salt permeable bipolar membrane area. Preferably, the heat melting point diameter is 5 mm, and the heat melting point occupies an area of 9% of the low-salt permeable bipolar membrane area.
[0040] In this embodiment, the thermal fusion process uses a heating tool to press the membrane surface or ultrasonic welding; the bipolar membrane at the thermal melting point loses its water dissociation performance, and the thermal melting point should not occupy too much area; the bipolar membrane water dissociation voltage is at a certain current density (typical test conditions are 500 A / m 2 or 1000 A / m 2 ) The potential difference formed on both sides of the bipolar membrane under the condition that the hot melting point occupies too much area and the effective area is reduced, so that the current density increases and the water dissociation voltage of the bipolar membrane increases accordingly; after comparing multiple embodiments, it is selected that the area occupied by the hot melting point accounts for about 9% of the bipolar membrane area.
[0041] The present application provides a method for preparing a low-salt permeability bipolar membrane, in which a first anion membrane layer is designed to be thin and does not contain a cross-linking agent. The membrane layer has low resistance and is in full contact with a cation membrane layer during the film-forming process, so that the bipolar membrane has a low water dissociation voltage and low selectivity. For this purpose, a second anion membrane layer with high selectivity and low salt permeability is further compounded, so that the final bipolar membrane achieves low salt permeability; the second anion membrane layer will not significantly increase the water dissociation voltage of the bipolar membrane; the first anion membrane layer and the cation membrane layer both contain styrene structural units, so that the first anion membrane layer and the cation membrane layer have a stronger bonding force, and the bipolar membrane is not easy to delaminate or bubble during use; the cation membrane layer uses a polyolefin support layer, the first anion membrane layer contains styrene or methyl styrene units, and the second anion membrane layer uses a polyolefin material, so that the membrane layers can be fused together through a thermal fusion process; the surface of the polyolefin support cloth of the cation membrane layer contains a non-woven fabric layer, so that the surface is rough or easy to polish to form a rough surface, which effectively increases the catalyst loading and enhances the bonding force between the first anion membrane layer and the cation membrane layer, forming a low water dissociation voltage bipolar membrane and the anion and cation membrane layers are not easy to separate. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0043] Figure 1 Schematic diagram of bipolar membrane structure and bipolar membrane water dissociation;
[0044] Figure 2 It is a schematic diagram of thermal melting point;
[0045] Figure 3 is the current-voltage curve.
[0046] Explanation of symbols in the figure:
[0047] 1. Low salt permeable bipolar membrane; 2. Cation membrane layer; 3. Catalytic layer; 4. First anion membrane layer; 5. Second anion membrane layer; 6. Thermal melting point. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clear, the present application is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0049] Example 1
[0050] (i) Preparation of a cationic membrane layer: 210 g of trimethylamine styrenesulfonate, 37 g of methacrylic acid, 57 g of p-divinylbenzene, 90 g of N-methylpyrrolidone and 1.5 g of azobisisobutyronitrile were mixed evenly to obtain a cationic membrane monomer solution; a polypropylene non-woven fabric layer was thermally bonded on both sides of a polypropylene microporous membrane (porosity of 40-70%) to obtain a substrate (thickness of 110 μm); the substrate was immersed in the cationic membrane monomer solution for 10 min to fully impregnate it, the substrate was taken out and placed between two polyethylene terephthalate films, the films were rolled to remove bubbles between the substrate and the films, and a cationic membrane composite was obtained, and then the cationic membrane composite was sandwiched between two pieces of glass and the two pieces of glass were sealed around to make the cationic membrane composite in a sealed state, and the sealed cationic membrane composite was heated at 80°C for 16 h to allow the initiator to initiate a polymerization reaction, and the two pieces of glass were removed and the two pieces of polyethylene terephthalate films were peeled off to obtain a cationic membrane layer 2;
[0051] (ii) Preparation of the catalytic layer: slowly add 3 g of chromium trichloride hexahydrate solution to 100 g of 1 mol / L sodium hydroxide solution, stir and keep at 90°C for 1 h to obtain a catalyst dispersion; grind one side of the cation layer 2 with sandpaper to make the surface rough, ultrasonically spray the catalyst dispersion on the surface and place it in a 60°C oven for 10 min to dry, and after the liquid evaporates, form a catalytic layer 3 on the surface of the cation layer 2;
[0052] (III) Preparation of the first anion film layer: 240 g of 1-vinyl-3-methylimidazolium iodide, 240 g of p-methylstyrene, 380 g of N,N-dimethylformamide and 5 g of azobisisobutyronitrile were mixed evenly, and the temperature was raised to 80°C under nitrogen protection and kept constant for 24 h to obtain a coating liquid; the coating liquid was coated on the catalyst layer 3, and placed in an oven at 80°C for 1 h to dry, forming a first anion film layer 4 on the surface of the catalyst layer 3 to obtain a composite membrane; the thickness of the first anion film layer 4 was 20 μm;
[0053] (IV) Preparation of the second anion membrane layer: 426 g of 1-vinyl-3-methylimidazolium iodide, 99 g of p-divinylbenzene, 219 g of N-methylpyrrolidone and 2.5 g of azobisisobutyronitrile were mixed evenly to obtain an anion membrane monomer solution; a polypropylene microporous membrane with a thickness of 70 μm was immersed in the anion membrane monomer solution for 10 min to fully impregnate it, the polypropylene microporous membrane was taken out and placed between two polyethylene terephthalate films, and the films were rolled to remove the bubbles between the polypropylene microporous membrane and the films to obtain an anion membrane composite; the anion membrane composite was then sandwiched between two pieces of glass and the two pieces of glass were sealed around to keep the anion membrane composite in a sealed state, the sealed anion membrane composite was heated at 80°C for 16 h to allow the initiator to initiate a polymerization reaction, and after being placed at a constant temperature for 10 h, the two pieces of glass were removed and the two films were peeled off to obtain the second anion membrane layer 5;
[0054] (V) Preparation of bipolar membrane: The second anion membrane layer 5 is thermally fused to the first anion membrane layer 4 of the composite membrane, and ultrasonic welding is used to form uniformly arranged hot melting points 6 with a diameter of 5 mm between the second anion membrane layer 5 and the first anion membrane layer 4. The center distance between each hot melting point 6 is 15 mm, and the area occupied by the hot melting points 6 is 9% of the area of the bipolar membrane; then the membrane is immersed in a 1 mol / L NaCl solution to obtain a low salt permeable bipolar membrane 1, the structure of which is as follows: Figure 1 shown.
[0055] Example 2
[0056] The present embodiment is different from the embodiment 1 in that, in the step (i) of preparing the cation layer 2, the ratio of the cation monomer solution is 210 g of styrene sulfonate pyridinium salt, 35 g of methacrylic acid, 52 g of p-divinylbenzene, 90 g of N-methylpyrrolidone and 1.5 g of azobisisobutyronitrile; in the step (iii) of preparing the first anion layer 4, the ratio of the coating solution is 240 g of 1-vinyl 3-propyl imidazole bromide, 240 g of p-methylstyrene, 380 g of N,N-dimethylformamide and 5 g of azobisisobutyronitrile; in the step (iv) of preparing the second anion layer 5, the ratio of the anion monomer solution is 426 g of 1-vinyl 3-propyl imidazole bromide, 107 g of p-divinylbenzene, 226 g of N-methylpyrrolidone and 2.7 g of azobisisobutyronitrile; the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0057] Example 3
[0058] The present embodiment is different from the embodiment 1 in that the composition of the cationic membrane monomer solution is: 210 g of trimethylamine styrenesulfonate, 70 g of p-divinylbenzene, 90 g of N-methylpyrrolidone and 1.5 g of azobisisobutyronitrile, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0059] Example 4
[0060] The present embodiment is different from the embodiment 1 in that the methacrylic acid in step (I) is replaced by acrylic acid, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0061] Example 5
[0062] The present embodiment is different from the embodiment 1 in that the polypropylene microporous membrane in step (i) is replaced by a polyethylene microporous membrane, and the polypropylene non-woven fabric layer is replaced by a polyethylene non-woven fabric layer. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0063] Example 6
[0064] The present embodiment is different from the embodiment 1 in that the polypropylene microporous membrane in step (i) is replaced by an ethylene and propylene copolymer microporous membrane, and the polypropylene non-woven fabric layer is replaced by an ethylene and propylene copolymer non-woven fabric layer. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0065] Example 7
[0066] The present embodiment is different from the embodiment 1 in that the polymerization reaction heating temperature in step (i) is 60° C., and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0067] Example 8
[0068] The present embodiment is different from the embodiment 1 in that the polymerization reaction heating temperature in step (I) is 100° C., and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0069] Example 9
[0070] The present embodiment is different from the embodiment 1 in that the heating time of the polymerization reaction in step (I) is 8 h, and the other operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0071] Example 10
[0072] The present embodiment is different from the embodiment 1 in that the heating time of the polymerization reaction in step (i) is 24 h, and the other operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0073] Embodiment 11
[0074] The present embodiment is different from the embodiment 1 in that the amount of methacrylic acid added in step (i) is 50 g, the molar ratio of methacrylic acid to trimethylammonium styrenesulfonate is 4:6, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0075] Example 12
[0076] The present embodiment is different from the embodiment 1 in that the amount of methacrylic acid added in step (i) is 19 g, the molar ratio of methacrylic acid to trimethylammonium styrenesulfonate is 2:8, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0077] Embodiment 13
[0078] The present embodiment is different from the embodiment 1 in that the amount of p-divinylbenzene added in step (i) is 28 g, the molar ratio of p-divinylbenzene to trimethylamine styrenesulfonate is 2:8, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0079] Embodiment 14
[0080] The present embodiment is different from the embodiment 1 in that the amount of p-divinylbenzene added in step (i) is 49 g, the molar ratio of p-divinylbenzene to trimethylamine styrenesulfonate is 3:7, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0081] Embodiment 15
[0082] The present embodiment is different from the embodiment 1 in that the amount of p-divinylbenzene added in step (i) is 76 g, the molar ratio of p-divinylbenzene to trimethylamine styrenesulfonate is 4:6, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0083] Example 16
[0084] The present embodiment is different from the embodiment 1 in that the polyethylene terephthalate film in step (i) is replaced by an aluminum sheet, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0085] Embodiment 17
[0086] The present embodiment is different from the embodiment 1 in that the trimethylamine styrenesulfonate in step (i) is replaced by triethylamine styrenesulfonate, N-methylpyrrolidone is replaced by N,N-dimethylformamide, and azobisisobutyronitrile is replaced by azobisisoheptylnitrile. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0087] Embodiment 18
[0088] The present embodiment is different from the embodiment 1 in that the trimethylamine styrenesulfonate in step (i) is replaced by N-methylimidazole styrenesulfonate, N-methylpyrrolidone is replaced by N,N-dimethylacetamide, and azobisisobutyronitrile is replaced by dibenzoyl peroxide. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0089] Embodiment 19
[0090] The present embodiment is different from the embodiment 1 in that the N-methylpyrrolidone in step (i) is replaced by dimethyl sulfoxide, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0091] Embodiment 20
[0092] The present embodiment is different from the embodiment 1 in that the chromium trichloride hexahydrate in step (ii) is replaced by ferric chloride at a concentration of 0.5%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0093] Embodiment 21
[0094] The present embodiment is different from the embodiment 1 in that the chromium trichloride hexahydrate in step (ii) is replaced with chromium sulfate at a concentration of 0.5%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0095] Embodiment 22
[0096] The present embodiment is different from the embodiment 1 in that the chromium trichloride hexahydrate in step (ii) is replaced with ferric nitrate at a concentration of 0.5%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0097] Embodiment 23
[0098] The present embodiment is different from the embodiment 1 in that the catalyst dispersion in step (ii) is ruthenium dioxide dispersed in pure water with a concentration of 2%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0099] Embodiment 24
[0100] The present embodiment is different from the embodiment 1 in that the catalyst dispersion in step (ii) is titanium dioxide dispersed in pure water at a concentration of 2%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0101] Embodiment 25
[0102] The present embodiment is different from the embodiment 1 in that the catalyst dispersion in step (ii) is tin dioxide dispersed in pure water at a concentration of 5%. The remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0103] Embodiment 26
[0104] The present embodiment is different from the embodiment 1 in that the 1-vinyl-3-methylimidazolium iodide in step (iii) is replaced with 1-vinyl-3-ethylimidazolium iodide, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0105] Embodiment 27
[0106] The present embodiment is different from the embodiment 1 in that the 1-vinyl-3-methylimidazolium iodide in step (iii) is replaced with 1-ethyl-4-vinylpyridine iodide, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0107] Embodiment 28
[0108] The present embodiment is different from the embodiment 1 in that the 1-vinyl-3-methylimidazolium iodide in step (iii) is replaced with 1-methyl-4-vinylpyridine iodide, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0109] Embodiment 29
[0110] The present embodiment is different from the embodiment 1 in that the 1-vinyl-3-methylimidazolium iodide in step (iii) is replaced with 1-propyl-4-vinylpyridinium bromide, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0111] Embodiment 30
[0112] The present embodiment is different from the embodiment 1 in that the p-methylstyrene in step (iii) is replaced by styrene, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0113] Embodiment 31
[0114] The present embodiment is different from the embodiment 1 in that the amount of p-methylstyrene added in step (iii) is 52 g, the molar ratio of p-methylstyrene to 1-vinyl-3-methylimidazolium iodide is 3:7, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0115] Embodiment 32
[0116] The present embodiment is different from the embodiment 1 in that the amount of p-methylstyrene added in step (iii) is 280 g, the molar ratio of p-methylstyrene to 1-vinyl-3-methylimidazolium iodide is 7:3, and the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0117] Embodiment 33
[0118] The present embodiment is different from the embodiment 1 in that the drying temperature in step (iii) is 90° C. and the drying time is 2 h; the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0119] Embodiment 34
[0120] The present embodiment is different from the embodiment 1 in that the drying temperature in step (iii) is 100° C. and the drying time is 0.5 h; the remaining operations are the same, and a low-salt permeable bipolar membrane 1 is obtained.
[0121] Embodiment 35
[0122] The present embodiment is different from the embodiment 1 in that the thickness of the first cathode membrane layer 4 is 10 μm; the remaining operations are the same, and a low-salt permeable bipolar membrane 1 is obtained.
[0123] Embodiment 36
[0124] The present embodiment is different from the embodiment 1 in that the thickness of the first cathode membrane layer 4 is 40 μm; the remaining operations are the same, and a low-salt permeable bipolar membrane 1 is obtained.
[0125] Embodiment 37
[0126] The present embodiment is different from the embodiment 1 in that the polymerization reaction is heated at 60° C. for 24 h in step (iv); the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0127] Embodiment 38
[0128] The present embodiment is different from the embodiment 1 in that the polymerization reaction is heated at a temperature of 100° C. for 4 h in step (iv); the remaining operations are the same to obtain a low-salt permeable bipolar membrane 1.
[0129] Embodiment 39
[0130] The present embodiment is different from the embodiment 1 in that the thermal melting point diameter in step (V) is 3 mm; the remaining operations are the same, and a low-salt permeable bipolar membrane 1 is obtained.
[0131] Embodiment 40
[0132] The present embodiment is different from the embodiment 1 in that the thermal melting point diameter in step (V) is 6 mm; the remaining operations are the same, and a low-salt permeable bipolar membrane 1 is obtained.
[0133] The bipolar membrane current-voltage curve test device has a 4-compartment structure. The low-salt permeable bipolar membrane 1 is placed in the center of the test cell, the positive membrane layer 2 faces the negative electrode, and the negative membrane layer of the bipolar membrane faces the positive electrode. 0.5 M NaCl solution is passed through both sides of the membrane. Ag / AgCl reference electrodes are placed on both sides of the membrane to measure the voltage. A direct current is applied through the titanium electrodes located at both ends of the test cell, and the current is gradually increased and the voltage between the two Ag / AgCl reference electrodes is monitored; the current-voltage curves of the bipolar membranes prepared in Example 1 and Example 2 are shown in FIG. Figure 3 As shown, the current-voltage curve of the commercial bipolar membrane was measured under the same conditions. The current density corresponding to the intersection of the tangent line from the ohmic region and the platform region of the current-voltage curve is the water dissociation current density of the bipolar membrane, which characterizes the salt permeation of the bipolar membrane water dissociation to produce acid and alkali; 200 A / m 2 The transmembrane voltage under current density characterizes the energy consumption of water dissociation to produce acid and base in bipolar membrane. The water dissociation current density of commercial membrane is about 30 A / m2 , at 200 A / m 2 The transmembrane voltage at the current density is about 1.05 V; the water dissociation current density of the bipolar membranes of Example 1 and Example 2 is about 20 A / m 2 , at 200 A / m 2 The transmembrane voltages under the current density were respectively about 1.05 V and 1.15 V. The water dissociation current density of the bipolar membranes of Example 1 and Example 2 was lower than that of the commercial membrane, indicating that the prepared bipolar membranes had very low salt permeation.
[0134] The experimental bipolar membrane electrodialysis equipment was equipped with the bipolar membrane of Example 1, commercial cation membrane and commercial anion membrane. The equipment was equipped with 10 membrane pairs, the membrane size was 10×20 cm, the effective size of the membrane was 7×12 cm, the thickness of the partition was 0.6 mm, 2 L of 10% sodium chloride solution was circulated in the salt chamber, and 1 L of pure water was passed into the acid chamber and the alkali chamber, respectively. The voltage and current of the regulated DC power supply were set to 25V and 6.4 A, respectively. The bipolar membrane electrodialysis equipment was terminated after running for 120 min. The average membrane pair voltage of the entire bipolar membrane electrodialysis experiment was 1.66 V, and the average current density was 669 A / m 2 , the concentration of hydrochloric acid produced was 2.85 mol / L, and the sodium ion content in the acid chamber was 502 ppm. Using a commercial bipolar membrane under the same conditions, the average membrane voltage of the entire experimental process was 1.75 V, and the average current density was 650 A / m 2 The hydrochloric acid concentration produced was 2.63 mol / L, and the sodium ion content in the acid chamber was 873 ppm. The hydrochloric acid concentration produced by the bipolar membrane of Example 1 was higher than that of the commercial membrane, and the sodium ion content in the acid was lower than that of the commercial membrane, indicating that the prepared bipolar membrane had very low salt permeation.
[0135] The present application provides a method for preparing a low-salt permeability bipolar membrane, comprising preparing a cation layer, preparing a catalytic layer, preparing a first anion layer, preparing a second anion layer and preparing a bipolar membrane; in view of the inherent characteristic that the anion layer is difficult to form a cross-linked structure in a casting process, the present application separately designs the high selectivity of the anion layer and the good intermediate interface layer formed by the anion and cation layers, after a water dissociation catalyst is coated on the surface of the cation layer, an anion membrane polymer solution is coated to form a thinner anion layer, and then a highly selective anion membrane is attached and each membrane layer is fixed together to form a whole by a hot melt process; the first anion layer is a thinner anion layer formed by coating, and the design focus is to make the bipolar membrane have a low water dissociation voltage, and the second anion layer is a highly selective anion layer, which ensures the low salt permeability of the bipolar membrane; the cation layer, the first anion layer and the second anion layer are all designed to be fused together by a hot melt process, and the prepared bipolar membrane has low salt permeability and low water dissociation voltage.
[0136] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0137] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a low-salt permeable bipolar membrane, characterized in that: The specific steps include: (i) preparing a cation membrane layer: preparing a cation membrane monomer solution, wherein the cation membrane monomer solution includes a cation membrane functional monomer, a cross-linking agent, an organic solvent and an initiator; soaking a substrate in the cation membrane monomer solution and then placing the substrate between two inert sheets, removing bubbles to obtain a cation membrane complex, and heating the cation membrane complex to perform a polymerization reaction; peeling off the inert sheets to obtain a cation membrane layer; (ii) preparing a catalytic layer: coating a catalyst dispersion on one side of the cation film layer to form a catalytic layer on the surface of the cation film layer; (iii) preparing the first anion membrane layer: coating the coating liquid prepared by solution polymerization of anion membrane functional monomers and anion membrane comonomers on the catalyst layer, and drying to form the first anion membrane layer on the surface of the catalyst layer to obtain a composite membrane; (IV) preparing the second anion membrane layer: preparing anion membrane monomer solution, wherein the anion membrane monomer solution includes anion membrane functional monomer, a cross-linking agent, an organic solvent and an initiator; soaking the microporous membrane in the anion membrane monomer solution and then placing the microporous membrane between two inert sheets, removing bubbles to obtain an anion membrane complex, and heating the anion membrane complex to perform a polymerization reaction; peeling off the inert sheets to obtain the second anion membrane layer; (V) Preparation of bipolar membrane: the second anion membrane layer is tightly attached to the first anion membrane layer of the composite membrane; a hot melting point is formed between the second anion membrane layer and the composite membrane through a hot melt process, thereby obtaining a low-salt permeable bipolar membrane.
2. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: Step (i) The cationic functional monomer is one of trimethylamine styrenesulfonate, triethylamine styrenesulfonate, pyridinium styrenesulfonate or N-methylimidazole styrenesulfonate; the cross-linking agent is p-divinylbenzene; the organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide; the initiator is one of azobisisobutyronitrile, azobisisoheptylnitrile or dibenzoyl peroxide; a cationic comonomer is added to the cationic monomer solution, the cationic comonomer is acrylic acid or methacrylic acid, and the molar ratio of the cationic comonomer to the cationic functional monomer is 0-4:10-6.
3. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: The preparation of the substrate in step (i) is as follows: non-woven fabric layers are bonded on both sides of a microporous membrane, wherein the material of the microporous membrane is polyethylene, polypropylene or a copolymer of ethylene and propylene, the material of the non-woven fabric layer is polyethylene, polypropylene or a copolymer of ethylene and propylene, and the porosity of the microporous membrane is 40-70%.
4. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: In step (i), the molar ratio of the crosslinking agent to the cationic functional monomer is 2-4:8-6; the heating temperature is 60-100°C, the time is 8-24h, and the material of the inert sheet is one of plastic, glass or metal.
5. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: Step (ii) The catalyst dispersion is prepared by dispersing one of chlorides, sulfates or nitrates of trivalent chromium or trivalent iron in an alkaline solution, or dispersing one of titanium dioxide, tin dioxide or ruthenium dioxide in pure water; the concentration of the catalyst dispersion is 0.5-5%.
6. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: The anionic membrane functional monomer is one of 1-methyl-4-vinylpyridinium iodide, 1-ethyl-4-vinylpyridinium iodide, 1-propyl-4-vinylpyridinium bromide, 1-vinyl-3-methylimidazolium iodide, 1-vinyl-3-ethylimidazolium iodide and 1-vinyl-3-propylimidazolium bromide.
7. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: In step (iii), the anion membrane comonomer is styrene or p-methylstyrene; the molar ratio of the anion membrane comonomer to the anion membrane functional monomer is 3-7: 7-3.
8. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: The drying temperature in step (iii) is 80-100°C and the drying time is 0.5-2 h; the thickness of the first cathode film layer is 10-40 μm.
9. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: In step (iv), the molar ratio of the crosslinking agent to the anionic membrane functional monomer is 2-5:8-5; the heating temperature is 60-100°C and the heating time is 4-24h.
10. The method for preparing a low-salt permeable bipolar membrane according to claim 1, characterized in that: In step (V), the diameter of the thermal melting point is 3-6 mm; the area occupied by the thermal melting point is 2-20% of the area of the low-salt permeable bipolar membrane.
Citation Information
Patent Citations
PROCESS FOR MANUFACTURING BIPOLAR MEMBRANES
DE3508206A1
Bipolar membrane for sepn. by electrodialysis - comprises anion- and cation-selective layers and intermediate ultra-thin layer of polyelectrolyte complex with excess acid or basic gps.
DE4026154A1
Novel bipolar membranes and process of manufacture
US4851100A
Bipolar membrane
US5401408A
Single-film membrane, process for obtaining it and use thereof
US5840192A